Development of an Algorithm for Determining of Genetic Risk at the Primary Healthcare Level - A New Tool for Primary Prevention: A Study Protocol - Selič Polona; Klemenc-Ketiš Zalika; Zelko Erika; Kravos Andrej; Rifel Janez; Makivić Irena; Poplas Susič Antonija; Tevžič Špela; Cerovič Metka; Peterlin Borut; Kopčavar Guček Nena (Sciendo, 2019)
Family history (FH) is an important part of the patients' medical history during preventive management at model family medicine practices (MFMP). It currently includes a one (or two) generational inquiry, predominately in terms of cardiovascular diseases, arterial hypertension, and diabetes, but not of other diseases with a probable genetic aetiology. Beside family history, no application-based algorithm is available to determine the risk level for specific chronic diseases in Slovenia.